2023
DOI: 10.1021/acs.molpharmaceut.2c00881
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene-Loaded Soluplus/Poloxamer 188 Mixed Micelles for Protection against Acetaminophen-Induced Acute Liver Injury

Abstract: Excessive acetaminophen (APAP) induces excess reactive oxygen species (ROS), leading to liver damage. Pterostilbene (PTE) has excellent antioxidant and anti-inflammatory activities, but poor solubility limits its biological activity. In this study, we prepared PTE-loaded Soluplus/poloxamer 188 mixed micelles (PTE-MMs), and the protective mechanism against APAP-induced liver injury was investigated. In vitro results showed that PTE-MMs protected H 2 O 2 -induced HepG2 cell proliferation inhibition, ROS accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The results revealed that PTS‐MMs exhibited promising therapeutic effects on APAP‐induced acute liver injury. These findings highlight the potential of the Soluplus/poloxamer 188 MM system to enhance the biological activity of PTS and its effectiveness in protecting and treating liver injuries (Dong et al, 2023).…”
Section: Nanotechnology Solutions As a Promising Practical Approach I...mentioning
confidence: 82%
See 1 more Smart Citation
“…The results revealed that PTS‐MMs exhibited promising therapeutic effects on APAP‐induced acute liver injury. These findings highlight the potential of the Soluplus/poloxamer 188 MM system to enhance the biological activity of PTS and its effectiveness in protecting and treating liver injuries (Dong et al, 2023).…”
Section: Nanotechnology Solutions As a Promising Practical Approach I...mentioning
confidence: 82%
“…This finding may serve as the basis for developing LUT for the treatment of oral candida infection (Zhou, Li, et al, 2021). Peritoneal metastases in colorectal cancer are difficult to and its effectiveness in protecting and treating liver injuries (Dong et al, 2023).…”
Section: Polymeric Micellesmentioning
confidence: 97%
“…In fact, STING regulates NEMO ubiquitination to activate IKKβ, leading to NF‐κB activation with subsequent TBK1‐dependent phosphorylation and nuclear translocation to upregulate expression of its target genes, including the iNOS gene 32,33,36 . Further potential explication for STING‐potentiated hepatic inflammation is the direct stimulatory effect of INF‐γ on iNOS expression 34 . The computational modeling data exhibited high computational inhibitory effect of EMPA against some proteins included in inflammation process the counteracting the effect of APAP.…”
Section: Discussionmentioning
confidence: 95%
“…Addition of a co-surfactant to micelle systems may help improve overall stability and drug solubility. Recently, Pluronic ® F68/Soluplus ® mixed micelles carrying pterostilbene were prepared as a strategy to leverage Pluronic ® F68 drug loading and stability [ 84 ]. Inspired by this, a series of Pluronic ® /Soluplus ® @VES-GEM mixed micelles were prepared, keeping the Soluplus ® concentration fixed and increasing the concentration of the Pluronic ® constituent, especially aiming at improving Pluronic ® F68 stability.…”
Section: Resultsmentioning
confidence: 99%